An Unusual Location of Subungual Warty Dyskeratoma: A Case Report and Review of the Literature - Elena Vargas-Laguna; Adrián Imbernón-Moya; Antonio Aguilar-Martínez; Fernando Burgos (Case Reports in Dermatological Medicine)
Warty dyskeratoma is an uncommon entity characterized by a solitary keratotic papule or nodule usually located in the head and neck of young adults. The histopathology shows a pattern of acantholytic dyskeratosis. We report a 32-year-old man who presented pain, serous exudation, a distal onycholysis with subungual hyperkeratosis, and roundish erythronychia in the nail plate of his left first toe 2 years ago. A histopathologic diagnosis of subungual warty dyskeratoma was made. When dealing with focal acantholytic dyskeratosis several differential diagnoses should be considered including Darier’s disease, transient focal acantholytic dyskeratosis or Grover disease, and Hailey-Hailey disease. We present an unusual location of warty dyskeratoma in the nail bed using a clinicohistopathological correlation for the diagnosis.